Pengembangan LKS Kelas 7 SMP Aritmetika Sosial dan Penggunaanya dalam Pembelajaran Blended Learning Tipe Flipped Classroom - Hobri, Hobri; Putri, Meilysa Ajeng Kartika; Murtikusuma, Randi Pratama; Oktavianingtyas, Ervin; Pambudi, Didik Sugeng (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
This Student Worksheet were structured and developed for grade sevenon Social Arithmetic and its used in flipped classroom blended learning. This Student Worksheetwas designed like an android application with codular. The purpose of this research is to develop social arithmetic worksheet which is valid, practical and effective for grade seven in flipped classroom blended learning. The development model used in developing this studentworksheets is Four D Model. Methode for conducting this research is the observation method to see the effectiveness and practically, the test method and questionnaire method used to see the effectiveness of student worksheet. The results of this study are the results of the Student Worksheet validation score that meet the valid criteria (3.6 out of 4.00) based on the results of the validator. This Student Worksheet obtained a very good conclusion and was declared practical (94.73%) based on observations of teacher activities. Student Worksheets with the subject of social arithmetic and their used in the flipped classroom blended learning is categorized as effective based on student test results (100%), observations of student activities (96.88%) and student response results (100%).